Solve for x
x=-z\left(-9y+6\sqrt{2y}-2\right)
y\geq 0\text{ and }-3\sqrt{y}+\sqrt{2}\geq 0\text{ and }z\neq 0
Solve for y
y=\frac{\left(-\sqrt{\frac{x}{z}}+\sqrt{2}\right)^{2}}{9}
\left(x\leq 0\text{ or }z>0\right)\text{ and }\left(z<0\text{ or }x\geq 0\right)\text{ and }z\neq 0\text{ and }-\sqrt{\frac{x}{z}}+\sqrt{2}\geq 0
Solve for x (complex solution)
x=-z\left(-9y+6\sqrt{2y}-2\right)
z\neq 0\text{ and }\left(y=\frac{2}{9}\text{ or }arg(-3\sqrt{y}+\sqrt{2})<\pi \right)
Solve for y (complex solution)
y=\frac{\left(-\sqrt{\frac{x}{z}}+\sqrt{2}\right)^{2}}{9}
\left(z=\frac{x}{2}\text{ and }x\neq 0\right)\text{ or }\left(z\neq 0\text{ and }arg(-\sqrt{\frac{x}{z}}+\sqrt{2})<\pi \right)
Share
Copied to clipboard
\sqrt{\frac{1}{z}x}+\sqrt{9y}-\sqrt{9y}=\sqrt{2}-\sqrt{9y}
Subtract \sqrt{9y} from both sides of the equation.
\sqrt{\frac{1}{z}x}=\sqrt{2}-\sqrt{9y}
Subtracting \sqrt{9y} from itself leaves 0.
\sqrt{\frac{1}{z}x}=-3\sqrt{y}+\sqrt{2}
Subtract \sqrt{9y} from \sqrt{2}.
\frac{1}{z}x=\left(-3\sqrt{y}+\sqrt{2}\right)^{2}
Square both sides of the equation.
\frac{\frac{1}{z}xz}{1}=\frac{\left(-3\sqrt{y}+\sqrt{2}\right)^{2}z}{1}
Divide both sides by z^{-1}.
x=\frac{\left(-3\sqrt{y}+\sqrt{2}\right)^{2}z}{1}
Dividing by z^{-1} undoes the multiplication by z^{-1}.
x=z\left(-3\sqrt{y}+\sqrt{2}\right)^{2}
Divide \left(\sqrt{2}-3\sqrt{y}\right)^{2} by z^{-1}.
\sqrt{9y}+\sqrt{\frac{x}{z}}-\sqrt{\frac{x}{z}}=\sqrt{2}-\sqrt{\frac{x}{z}}
Subtract \sqrt{xz^{-1}} from both sides of the equation.
\sqrt{9y}=\sqrt{2}-\sqrt{\frac{x}{z}}
Subtracting \sqrt{xz^{-1}} from itself leaves 0.
\sqrt{9y}=-\sqrt{\frac{x}{z}}+\sqrt{2}
Subtract \sqrt{xz^{-1}} from \sqrt{2}.
9y=\left(-\sqrt{\frac{x}{z}}+\sqrt{2}\right)^{2}
Square both sides of the equation.
\frac{9y}{9}=\frac{\left(-\sqrt{\frac{x}{z}}+\sqrt{2}\right)^{2}}{9}
Divide both sides by 9.
y=\frac{\left(-\sqrt{\frac{x}{z}}+\sqrt{2}\right)^{2}}{9}
Dividing by 9 undoes the multiplication by 9.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}